DEMONSTRASI PENINGKATAN KREATIFITAS POT BUNGA PADA LANSIA DI DESA KRANGGANHARJO - Suryani; Wahyu Riniasih; Eva Latifatul Uzza; Yugi Febia; Mutmainah Indah Puspitasar; Anisy Nurul Janah; Dina Septika Dewi Khofifa (LPPM AN Nuur, 2023)
Background: Old age is seen as a period of decline, a time when elderly people (elderly) feel the decline that occurs to them both physically and psychologically. Elderly people experience and interpret old age in different ways. Using used goods is felt to be beneficial for the elderly themselves, the environment and their families Method: The implementation method is training in making flower pots from used gallons. This community service is carried out by helping organize creative activities for processing used materials, where this activity involves 3 groups in one village and the An-Nuur Purwodadi University KKN team in Glonggong Hamlet. Results: Based on the evaluation results, it was found that 9 elderly people had participated in the service activities with enthusiasm or 85% of all elderly people in Glonggong Hamlet and 100% of the participants who attended felt more relaxed and happy with the implementation of creative activities for the elderly. Conclusion: Community service results from 9 participants, 100% were able to take part in training activities and were able to produce 3 flower pots from used gallons.